The Influence of Teachers’ Teaching Skills and School Organizational Culture on Students’Achievement - Anisah Anisah; Agus Widyantoro (Lingua Pedagogia, 2019)
This research aims to investigate the effect of the teachers’ teaching skills and school organizational culture on the students’ learning achievement in English. The research was ex-post facto quantitative. The population comprised all Year VIII students of six SMPN’s in the District of Sintang. A sample of 260 students from six schools based on Krejcie and Morgan formula  was established using the cluster sampling technique. The data were collected through Likert-scale questionnaires. The validity of the instrument was assessed in terms of content validity. The data were analyzed using the multiple linier regression analysis with two independent variables, anova test, and test of multiple linier regression analysis prerequisites (test of multicolinearity, heteroscedasticity, normality, and linierity). The results of the regression testing on the variable of teachers’ teaching skills show the coefficient β = 0.030, p 0.0001 (significant). The variable of school organizational culture shows the coefficient β = 0.014, p 0.0001 (significant). The effect of these two variables together showsR² = 0.155, Ftest = 23.593, p 0.0001 (significant). It is concluded that both teachers’ teaching skills and school organizational culture collectively have a significant effect on the English learning achievement. Keywords: teachers’ teaching skills, school organizational culture, English learning achievement